The population ecology and conservation of Charadrius plovers - Colwell, Mark A.; Haig, Susan M. (Boca Raton : CRC Press, 2019)
The 40 or so species of beach-loving plovers (genus Charadrius) comprise a diverse group of shorebirds found around the world. Most of these species are challenged by changing climates and other human-related development activities, yet they provide key insights into basic ecological and evolutionary processes. The expert international contributors take a comparative approach, presenting examples from many worldwide plover studies and synthesizing the group's most pressing and important topics. The book further presents an emphasis on full life-cycle biology, including the importance of examining migratory connectivity issues, even for non-migratory plovers. Key Features Serves as a fundamental resource for conservation practitioners Detailed overview of a widely distributed group of shorebirds Authored by renowned specialists who present theoretical and applied perspectives Emphasis on comparative and synthetic approach in all chapters Related Titles McComb, B. et al. Monitoring Animal Populations and Their Habitats: A Practitioner's Guide (ISBN 978-0-4291-3827-0). Garvey, J. E. & M. R. Whiles. Trophic Ecology (ISBN 978-1-4987-5846-8). Dewdney, A. K. Stochastic Communities: A Mathematical Theory of Biodiversity (ISBN 978-1-1381-9702-2).
OCLC-licensed vendor bibliographic record.
Keywords: Charadrius -- Ecology; Charadrius -- Conservation; NATURE / Animals; NATURE / Ecology; SCIENCE / Life Sciences / Evolution